2018
DOI: 10.1002/mus.26151
|View full text |Cite
|
Sign up to set email alerts
|

Muscle‐ultrasound evaluation in healthy pediatric subjects: Age‐related normative data

Abstract: Our MUS study provides new data on physiological muscle structural changes in healthy children to address the limited available references in this age group. Muscle Nerve 58: 245-250, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 17 publications
1
10
0
6
Order By: Relevance
“…The significant correlation between age and muscle architecture parameters found in this study is consistent with a previous report [13] that showed that pennation angle values increase from birth and stabilize after adolescence. Our results are also consistent with another study [14] wherein it was found that the muscle thickness increases with age from 2 to 16 years in healthy children. The increase in the muscle architecture parameters with age may be due to the ongoing maturation and development of children as the muscle size increases.…”
Section: Discussionsupporting
confidence: 93%
“…The significant correlation between age and muscle architecture parameters found in this study is consistent with a previous report [13] that showed that pennation angle values increase from birth and stabilize after adolescence. Our results are also consistent with another study [14] wherein it was found that the muscle thickness increases with age from 2 to 16 years in healthy children. The increase in the muscle architecture parameters with age may be due to the ongoing maturation and development of children as the muscle size increases.…”
Section: Discussionsupporting
confidence: 93%
“…The systematic difference in echodensity between mechanically ventilated patients and healthy subjects may arise from differences in age or chronic comorbidity between groups, apart from any acute muscle injury in mechanically ventilated patients. Both comorbidity and age have been shown to affect muscle echodensity [8,28,40]. These factors might account for some of the observed differences between patients and healthy subjects in this study; to mitigate confounding in this comparison, we analyzed the change in echodensity within subjects over time and normalized patients to their baseline echodensity.…”
Section: Discussionmentioning
confidence: 99%
“…Although we are reluctant to over-interpret these findings, it is tempting to hypothesize that these muscles could still reveal the same developmental trend, after a short delay. For instance, in this respect Lori et al had reported that biceps and tibialis anterior muscles do reveal an MUD increase, after the 2 nd year of life [20]. However, additional data are needed to substantiate this hypothesis to further extent.…”
Section: Fetal-mud-ratiomentioning
confidence: 92%
“…All lengths and weights of the included fetuses and newborns were within the normal range of the prenatal Hadlock growth curve and the postnatal growth curve [22]. Since weight and length of healthy children do not influence MUD [15,20], individual values are not specified. For personal reasons related to traveling and domestic zest, parents of eight fetally included children decided to stop with their longitudinal participation after delivery.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation